2013
DOI: 10.2174/09298673113209990163
|View full text |Cite
|
Sign up to set email alerts
|

Human Galectin-3 Selective and High Affinity Inhibitors. Present State and Future Perspectives

Abstract: Over the last decade an increasing number of studies have been published reporting on the inhibitory potency or selectivity that several types of ligands show against human galectin-3 (hGal-3). The reason for this interest lies in the many important roles galectins play both in intra and extra-cellular functions. Among galectins, galectin-3 stands out because it is the only known member of its subfamily in mammals, is small and monomeric but capable of aggregating, and is known to be involved in a large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…First, in-depth research into the functional network of Gal-3 associated with the mitogen-activated protein kinase/ERK1/2 pathway, caspase activation, b-catenin/GSK-3b signaling, EMT process, and TGF-b/Smads signaling will help clarify the pathogenesis of organ fibrosis. Second, the compounds that have hydrophilic substituent at the taloside O2 position may enhance specificity for binding human Gal-3, and further research involving these selective and high-affinity Gal-3 inhibitors may be an effective route to attenuating fibrosis (Téllez-Sanz et al, 2013). Thirdly, it is pivotal to determine whether the inhibitors used should target Gal-3 in extra-or intracellular space in different types of fibrosis.…”
Section: Gal-3 In Fibrotic Diseasesmentioning
confidence: 99%
“…First, in-depth research into the functional network of Gal-3 associated with the mitogen-activated protein kinase/ERK1/2 pathway, caspase activation, b-catenin/GSK-3b signaling, EMT process, and TGF-b/Smads signaling will help clarify the pathogenesis of organ fibrosis. Second, the compounds that have hydrophilic substituent at the taloside O2 position may enhance specificity for binding human Gal-3, and further research involving these selective and high-affinity Gal-3 inhibitors may be an effective route to attenuating fibrosis (Téllez-Sanz et al, 2013). Thirdly, it is pivotal to determine whether the inhibitors used should target Gal-3 in extra-or intracellular space in different types of fibrosis.…”
Section: Gal-3 In Fibrotic Diseasesmentioning
confidence: 99%
“…Binding affinities have been reported for a series of carbohydrate-based ligands to galectin-3, which binds to lactose significantly better than to galactose or to N -acetylgalactosamine but does not bind to mannose [2224]. Both the glycan ligand and the topological display on the cell surface are required for high affinity, selective binding of galectins, as demonstrated in galectin binding studies with neuroblastoma cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the review presented here, other recent reviews are informative although focus on narrower aspects and consequently are overall less comprehensive. [42,43,132,133] Galactose-Based Inhibitors Despite galactose being the essential binding moiety for galectins, the actual binding affinity for galactose is only ,3-10 mM while disaccharides such as lactose show affinities in the range of 90-500 mM. [49] However, because saccharidebased inhibitors are hydrophilic, glycolytically unstable, and are not able to effectively cross the plasma membrane, the glucose (Glc) of lactose was replaced by thio-linked hydrophobic, aromatic groups and the resulting compounds were able to achieve 140-170 mM affinity, about the same as that of disaccharide lactosides, against galectin-7 (Fig.…”
Section: Modified Saccharidesmentioning
confidence: 99%
“…[42,43] The ability of galectins to form dimers and oligomers have been exploited by multivalent inhibitors [44] and highly glycosylated natural products. [45,46] In addition, several peptide-based inhibitors and peptidomimetics have been found that have certain levels of efficacy.…”
Section: Introductionmentioning
confidence: 99%